Teaching Performance in Relation to Emotional Intelligence among English Student-Teachers in the Teacher-Education Program in Hodeidah, Yemen - Ezzi, Nemah Abdullah Ayash (American Journal of Education and Learning, 2019)
This study basically aims to determine if higher teaching performance in the practicum courses was positively correlated to higher emotional intelligence among male and female ‎student-teachers, who enrolled in the English Department of the Faculty of Education at Hodeidah University. It also investigates gender differences in EI among the third and fourth-year student-teachers, and whether they are aware of the concept of EI and its influence on learning and teaching English. ‎It focuses on a sample of 160 English student-teachers: 60 of them are in the third-year level and 100 are in the fourth year. Out of 160, 30 are males plus 130 females. Bar-On and Parker (2000) 60-item Emotional Quotient Inventory (EQ-I) is used to measure students’ EI. Also, student-teachers’ end-semester marks in the courses of teaching practicum I & II are used. The findings revealed that the participants are unaware of EI and its significance in the learning/teaching processes. Also, they do have a good level of teaching performance and a quite high level of EI as measured by Bar-On & Parker 60-item EQ-I but ‎no significant correlation found between them. ‎Therefore, EI isn’t a significant predictor ‎of the student-teachers’ good ‎performance in teaching. Furthermore, gender differences in the student-teachers’ EI‎ are so simple and not of great significance. ‎This study helps to raise the instructors’ and student-teachers’ awareness of EI and its influence on teaching effectiveness. It further recommends that EI could be increased through the inclusion of it as a curricular component.